Thoracic Trauma in Earthquakes - Ağkoç, Melek; Turna, Akif (Cerrahpaşa Medical Journal, 2023)
Major earthquakes continue to be one of the most devastating disasters for mankind. Severe thoracic injuries seen in earthquake victims frequently lead to high mortality rates and significant multisystem trauma, with approximately 10% of casualties from severe earthquakes suffering from chest and lung injuries. Blunt trauma is the main cause of these injuries, which can be treated with vital but straightforward interventions if the victim is assessed promptly. After the initial assessment and securing of the airway, breathing, and circulation, it is crucial to identify any life-threatening injuries through a thorough physical examination. A comprehensive understanding of the primary pathophysiology behind lethal thoracic injuries is crucial for their effective treatment. Cite this article as: Ağkoç M, Turna A. Thoracic trauma in earthquakes. Cerrahpaşa Med J 2023;47(S1):64-68.